Delinquent behavior and dating violence among Latinx youth: a test of Gover's theoretical model of violent victimization - Zavala, Egbert (Journal of family violence, 2023)
Almost two decades ago, Gover articulated a theoretical model suggesting that the relationship between social ties and negative emotions on dating violence victimization occurs indirectly through risky behavior. To date, no study has attempted to apply this framework to dating violence victimization experienced by Latinx youth. Cultural influences such as familism may provide the necessary social ties needed to divert youth from delinquent behavior, while also lessening adverse emotions due to possible negative experiences. Using data collected from the Dating Violence Among Latino Adolescents (DAVILA) Study, this research investigated whether delinquent behavior mediated the relationships between social ties (enculturation and family support), and negative emotions (hostility, anxiety, and depression) on dating violence victimization. Results obtained from logistics regression analyses showed that only hostility had a positive and significant relationship to dating violence victimization. The indirect effect of enculturation on dating violence victimization through delinquency is not statistically significant. However, the indirect effects of family support, hostility, anxiety, and depression on dating violence victimization through delinquency are statistically significant, indicating that delinquency mediated the effects of family support, hostility, anxiety, and depression on dating violence victimization. These results provide partial support for Gover’s theoretical framework. Treatment and prevention programs aimed at reducing hostility may minimize the occurrence of dating violence victimization in this study population.